2021
DOI: 10.3389/fphys.2021.618582
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Protective Effects of Artemisia campestris Essential Oil Against Chlorpyrifos-Induced Kidney and Liver Injuries in Rats

Abstract: This study is aimed to elucidate the possible antioxidant and protective effects of Artemisia campestris essential oil (ACEO) against the deleterious effects of chlorpyrifos (CPF) in rats. The in vivo study revealed increases in aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), and alkaline phosphatase (ALP) activities and the serum contents of creatinine, urea, uric acid, cholesterol, triglycerides, low density lipoproteins (LDL), and glucose in rats treated with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
5
7
0
Order By: Relevance
“…The protective effect of A. campestris essential oil could be attributed to its anti-oxidant potential. Similar results were obtained by Saoudi et al 16 who determined the protective effect of A. campestris essential oil against chlorpyrifos-induced kidney injury in rats. Akrout et al 63 found that A. campestris essential oil was dominated by β-pinene, p-cymene, and α-pinene.…”
Section: Artemisia Campestrissupporting
confidence: 89%
“…The protective effect of A. campestris essential oil could be attributed to its anti-oxidant potential. Similar results were obtained by Saoudi et al 16 who determined the protective effect of A. campestris essential oil against chlorpyrifos-induced kidney injury in rats. Akrout et al 63 found that A. campestris essential oil was dominated by β-pinene, p-cymene, and α-pinene.…”
Section: Artemisia Campestrissupporting
confidence: 89%
“…Over the years, medicinal plants have been used to develop a variety of formulations that combat injuries such as wounds, burns and cuts [ 15 ]. Several ethno-medicinal plants have been used for medicinal applications thanks to their wide biological activities and medicinal applications due to counteracting oxidative stress potential, lesser costs and high safety margins [ 16 , 17 , 18 ]. Plant extracts are known to exhibit many pharmacological properties (anti-hyperlipidemic, anti-proliferative, and immunomodulatory, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts are known to exhibit many pharmacological properties (anti-hyperlipidemic, anti-proliferative, and immunomodulatory, etc.) through the multitude amounts of natural polyphenolic antioxidants [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia herbs contain hundreds of bioactive molecules including artemisinin and its derivatives that were effectively used to counteract malaria (Bora, Sharma, 2011;Kursat et al, 2015;Lis, Kowal, 2015;Nigam et al, 2019). These substances were actually reported to be potentially effective against several health problems (Kursat et al, 2015;Saoudi et al, 2017;Saoudi et al, 2021). Interestingly, the screening of Artemisia extracts proved that many derivatives such as artemisinin, kaempferol and rutin, and whole aerial parts extracts of Artemisia species exert virucidal effects against diverse types of viruses, including coronaviruses (Arbab et al, 2017 al., 2017;Cheng et al, 2004;D'Alessandro et al, 2020;Han et al, 2015;Ivanescu, Miron, Corciova, 2015;Kim, Jeon, Ko, 2001;Lai et al, 2007;Li et al, 2005;Lubbe et al, 2012;Ma, Nakamura, Hattori, 2001;McCutcheon et al, 1995;Mitrocotsa et al, 2000;Romero et al, 2006;Sinico et al, 2005).…”
Section: Antiviral Potential Of Artemisia Herbsmentioning
confidence: 99%